Introduction: Religion, culture, society: readings in the humanities and the revealed knowledge - Quayum, Mohammad Abdul (Silverfish Books, 2017)
An introductory chapter for the book that introduces the work generally, outlines its scope and methodology and provides an overview of the chapters. It also highlights the book's strengths and its limitations, and articulates how it could enhance our understanding of Islam, Islamic traditions and cultures and Muslim societies, as well as some non-Muslim Asian cultures.